Effect of Extended π-Conjugation of Central Cores on Photovoltaic Properties of Asymmetric Wide-Bandgap Nonfullerene Acceptors - Xia, Tian; Li, Chao; Ryu, Hwa Sook; Sun, Xiaobo; Woo, Han Young; Sun, Yanming (Organic Materials, 2020)
Tremendous efforts have been dedicated to develop low-bandgap nonfullerene acceptors (NFAs) for organic solar cells (OSCs). In comparison, the NFAs with a wide bandgap (WBG) have received less attention. Here, three novel acceptor–donor–acceptor type WBG NFAs (TPT-T, TPTT-T, and TPTTT-T) have been designed and synthesized with different fused central cores by varying the π-conjugation length and molecular structures, which all exhibit wide optical bandgaps over 1.8 eV. The successive π-conjugation extension of electron-donating central cores (from TPT-T to TPTT-T and to TPTTT-T) induces red-shifted absorption spectra, lower optical bandgap, and enhanced electron mobility simultaneously. As a result, the optimized OSC devices based on TPTTT-T:PBT1-C achieved a power conversion efficiency of 7.42%, which was higher than those of PBT1-C:TPTT-T (6.93%) and PBT1-C:TPT-T (6.11%) based devices. These results indicate that extending the molecular π-conjugation structure is an effective strategy to design efficient NFAs for OSCs.
Keywords: organic solar cells; nonfullerene acceptors; π-conjugation; wide-bandgap; power conversion efficiency